ANALISIS STRUKTURAL PADA ANTOLOGI PUISI HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO - Heryanti, Sintia Putri; Agustiani, Tanti (Universitas Islam Sumatera Utara, 2024)
This study uses an anthology of poetry by Sapardi Djoko Damono entitled Rain in June. This study will use the poetry anthology Rain in June as the object of research. The poetry anthology Rain in the Month of June consists of 102 titles of poems written between 1959-1994. Meanwhile, the poems that will be used as research objects only consist of three poems with the titles